The Academy of Oncology Nurse & Patient Navigators and the American Cancer Society Survey: Collaboration on Building and Sustaining Local Navigator Networks. - Gentry, Sharon S. (Journal of Oncology Navigation & Survivorship, 2021)
Background: Since 2015, the Academy of Oncology Nurse & Patient Navigators (AONN+) has encouraged local navigator network (LNN) formation in communities. A network is a group of navigators composed of anyone working in or supportive of the navigation role who chooses to meet in their local region to share strategies, experiences, and resources to increase empowerment and a sense of community. The LNN leader is required to be a member of AONN+ and hold 4 meetings throughout the year. In 2019, the American Cancer Society (ACS) received a Merck Foundation grant to develop a paper outlining effective strategies for the development, implementation, and sustainability of LNNs. The navigation leaders from ACS reached out to AONN+ leadership to collaborate on the development of the paper. Purpose: To understand the experiences of existing AONN+ LNNs, including their beginnings, challenges, and contributing factors to their success to assist ACS with their grant deliverable and support the growth and development of AONN+ LNNs. Methods: A 45-item multiple-choice and open-ended survey was developed by the national AONN+ LNN liaisons and ACS leaders to capture LNN composition and meeting structure, as well as successes and best practices in implementing, developing, and sustaining networking. In 2019, a 20-minute blinded survey was e-mailed to the leaders of LNN networks that had been operational for at least 1 year, and each leader was given the opportunity to respond separately over a 2-week period. Eleven LNNs have coleaders, therefore, 34 surveys were e-mailed to LNN leaders representing 23 LNNs. Results: Twenty-three surveys were completed representing 17 LNNs for a 68% leader response rate. Leaders in the surveys noted that AONN+ mentorship, program champions such as directors or navigators, as well as organized leadership skills were critical to successful implementation. For sustainability, membership "buyin, pharmaceutical meeting support, and media communication were vital." Discussion: In addition to these key factors, leaders supported the development of a toolkit to supplement the current AONN+ LNN online resources to improve mentoring, network leader training, and networking opportunities among leaders to help facilitate mentoring, and sharing of best practices and lessons learned. Conclusion: AONN+ LNN leader survey responses provided a rich understanding of network implementation and sustainability lessons learned that can be shared with other leaders to facilitate success in local settings.